Automated and controlled mechanical stimulation and functional imaging in vivo in C. elegans. Issue 15 (29th June 2017) - Cho, Yongmin; Porto, Daniel A.; Hwang, Hyundoo; Grundy, Laura J.; Schafer, William R.; Lu, Hang
Abstract : A new automated microfluidic platform can deliver a wide range of mechanical stimuli for functional neural imaging in C. elegans . Abstract : C. elegans is a useful genetic model system for investigating mechanisms involved in sensory behavior which are potentially relevant to human diseases. While utilities of advanced techniques such as microfluidics have accelerated some areas of C. elegans sensory biology such as chemosensation, studies of mechanosensation conventionally require immobilization by glue and manual delivery of stimuli, leading to low experimental throughput and high variability. Here we present a microfluidic platform that precisely and robustly delivers a wide range of mechanical stimuli and can also be used in conjunction with functional imaging and optical interrogation techniques. The platform is fully automated, thereby greatly enhancing the throughput and robustness of experiments. We show that the behavior of the well-known gentle and harsh touch neurons and their receptive fields can be recapitulated. Using calcium dynamics as a read-out, we demonstrate its ability to perform a drug screen in vivo . We envision that this system will be able to greatly accelerate the discovery of genes and molecules involved in mechanosensation and multimodal sensory behavior, as well as the discovery of therapeutics for related diseases.